The Literary and Scholarly Contributions of Al-Khatib al-Bhagdadi: الخطيب البغدادی کی ادبی اور علمی خدمات - Shahzadi, Dr. Imrana; Sidra, Sidra (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Al-Khatib al-Baghdadi was a great scholar, hadith scholar, and historian of Islamic history who gave a new color to Islamic sciences through his academic services. His research and writings are a beacon of light for researchers and students not only in his time but also today. The article examines in detail the academic and literary services, writings, research methods, and their impact of Al-Khatib al-Baghdadi.